Trabalho, corpo e formação humana: um exame sobre o complexo social da educação física em concepções pedagógicas no Brasil - Oliveira, Rogério Paes de (2022)
Brazilian physical education presents a varied chart of concepts and prepositions in an attempt to answer what is physical education and what is its social function. Among these conceptions and approaches, we can notice that three large groups emerge. The first concerns the biological determination of the body and the social function of physical education, the second refers to the determination of consciousness; and the third group, to physical education as body language. In this sense, discussing physical education as a complex of the social being means understanding, in its details, the ontological genesis of physical education and how it becomes part of the activity of forming the social being, which makes us concretely question: The action body in the vital activity of work makes physical education a social complex? And what is the relation of autonomy and dependence to the work complex that physical education has? This research aims to examine physical education as a social complex, scrutinizing how the participation of bodily action in the act of work makes work a determining factor in the production of the body. To underpin this understanding, we have, with a theoretical-philosophical-methodological foundation, the assumptions of Historical Materialism, founded by Karl Marx and Friedrich Engels, as well as its ontological recovery, made by the Hungarian revolutionary theorist György Lukács. Thus, we defend the present thesis of bodily need and physical education as necessary in the act of work. Following Marx and Engels, we believe that the production of existence is the key to understanding the historical and provisional essence of social being.